PENGARUH KREDIT PERBANKAN TERHADAP PERTUMBUHAN INDUSTRI MANUFAKTUR DALAM MENUNJANG PERTUMBUHAN EKONOMI INDONESIA - Fithriyah, Zulfita; Malik, Nazaruddin (Jurnal Ekonomi Pembangunan, 2010)
This research works through about influence between banking credit insuranceansies with industrial growth of manufacture. Besides also studies about vesting influence of credit insuranceansi to economic growth in Indonesia. Based on research done, obtained result that level of credit insuranceansi given to manufacture industry will affect at improvement of output at company. So equally, the many vestings of credit insuranceansi compares linear with industrial improvement of manufacture. At research hereinafter, happened the relation of concurrent between industrial growths of manufacture with chartered investment counsel growth. Where when industrial growth of manufacture increased hence will cause improvement at chartered investment counsel growth. Manufacture industry is one of economic sector, which if manufacture industry increased hence its the contribution is ever greater to chartered investment counsel growth. So growth of chartered investment counsel can increase